Genetic Variations of CARMN Modulate Glioma Susceptibility and Prognosis in a Chinese Han Population - Xi M; Zhang G; Wang L; Chen H; Gao L; Zhang L; Yang Z; Shi H (Dove Medical Press, 2022)
Min Xi,1 Gang Zhang,1 Liang Wang,2 Hu Chen,2 Li Gao,2 Luyi Zhang,1 Zhangkai Yang,1 Hangyu Shi1 1Department of Neurosurgery, Xi'an Children's Hospital, Xi'an, 710043, People's Republic of China; 2Department of Neurosurgery, Tangdu Hospital, Air Force Medical University, Xi'an, 710038, People's Republic of ChinaCorrespondence: Hangyu Shi, Department of Neurosurgery, Xi'an Children's Hospital, #69, Xijuyuan Lane, Lianhu District, Xi'an, 710043, Shaanxi, People's Republic of China, Tel/Fax +86-15202910508, Email shihangyu723@aliyun.comBackground: This study aimed to evaluate the relationship between CARMN polymorphisms and glioma risk and prognosis in a Chinese Han population.Methods: Seven single nucleotide polymorphisms (SNPs) in CARMN were genotyped among 592 glioma patients and 502 healthy controls. Log-additive models were used for risk assessment by the odds ratios (ORs) and 95% confidence intervals (CIs). Univariate and multivariate Cox regression analysis was applied to calculate Hazard ratios (HRs) and 95% CIs for prognosis assessment.Results: CARMN rs13177623 was a protective factor for glioma susceptibility (OR = 0.78, p = 0.043). In addition, rs13177623, rs11168100, rs12654195 and rs17796757 were associated with the risk of glioma among the subgroup stratified by age or gender. We also found that G rs13177623G rs12654195 haplotype was related to the decreased risk of glioma (OR = 0.61, p = 0.005). Importantly, rs13177623 [overall survival (OS): HR = 0.83, p = 0.047, and progression free survival (PFS): HR = 0.82, p = 0.031], rs12654195 (OS: HR = 0.64, p = 0.005 and PFS: HR = 0.65, p = 0.007) and rs11168100 (OS: HR = 0.71, p = 0.035) were associated with a better prognosis for glioma, especially in grade I-II glioma. In patients with grade III-IV glioma, rs17796757 polymorphism presented an improved OS.Conclusion: Our results firstly reported the contribution of CARMN variants (rs11168100, rs12654195, rs13177623, and rs17796757) to the susceptibility and prognosis of glioma in a Chinese Han population, which provided a novel insight on the relationship between CARMN gene and glioma tumorigenesis.Keywords: glioma, CARMN variants, susceptibility, prognosis, genetic variations